Language Policy for International Students in Ukrainian Higher Education Institutions - Zaichko, Vladyslava (Studia Warmińskie, 2021)
The article analyzes the features of language adaptation of foreign applicants in Higher Education Institutions of Ukraine, in particular, language orientation, problems of adaptation of foreigners in Ukrainian universities, the level of involvement in scientific and socio-cultural activities. The available empirical material makes it possible to identify the following types of foreign applicants: The first (dominant) type English-oriented «pragmatists». These students are active in both academic and research work, take an active part in the life of the university, mostly from Africa (Algeria, Nigeria, etc.), Asia (China, India, etc.) and South America (Ecuador, etc.). The second type consists of Russian-oriented «phlegmatics». These students show almost no extracurricular activity, they are mostly students from Turkmenistan, Uzbekistan, other post-Soviet countries, as well as from Turkey. The third is foreign students who are Ukrainian-oriented «dreamers». This is a heterogeneous group, both geographically and nationally. They have studied the Ukrainian language specifically to study in Ukraine. The main problem, as our research has shown, is the extremely low level of proficiency in foreign applicants who come to Ukraine as languages of international communication (primarily English). The same applies to most teachers of Ukrainian universities who work with these students, as well as the lack of teaching materials in English. It is recommended to divide the courses for foreign applicants by levels. One of the possible guidelines of the optimal language policy is the Finnish model, which provides for learning English, and for those who master the Finnish language – learning is free and there is an opportunity to receive a scholarship.